Taking sides - Soto, Gary. (Orlando, Fla. : Harcourt, Inc., 1992)
Fourteen-year-old Lincoln Mendoza, an aspiring basketball player, must come to terms with his divided loyalties when he moves from the Hispanic inner city to a white suburban neighborhood.
School Library Journal.
Wilson's Children.
Wilson's Junior High School.
5.7
5-8
Keywords: Basketball -- Fiction; Hispanic Americans -- Fiction; Schools -- Fiction; Single-parent families -- Fiction; Basketball -- Fiction; Hispanic Americans -- Fiction; School stories; Single-parent families -- Fiction